Kritik atas Fikih Lintas Agama: Studi atas Pemikiran Kaum Revivalis - Siti Hardianti Liputo; Sofyan A. P. Kau (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2019)
This paper explains the revivalist Islamic criticism of the views of the Paramadina Writers Team which permits interfaith marriages and permissibility of inheritance of different religions. This research is a library research with the main data source is the book Fiqh Lintas Agama: Membangun Masyarakat Inklusif-Pluralis. The results showed that Islamic revivalists argued that the history of Mu’azd and Muawiyah which was used as a reference by the Paramadina Writers Team did not agree on its validity compared to the history which forbids a Muslim from inheriting infidels. Whereas giving precedence to an agreed proposition of validity is more important to be held against than an argument whose validity is not agreed upon. Choosing a majority opinion over the opinion of a minority is more prioritized. The case where the majority of scholars forbid interfaith marriages is haram because of the textual statements of the verse, except marriages with the ahl al-kitab. That skill is also an emergency. Even the adverse effects of interfaith marriages must take precedence over benefits.